Localizing the Southern Ocean biogeochemical divide - Xie, Y; Tamsitt, V; Lennart Bach (2022)
The meridional overturning circulation consists of an upper and lower cell. The Southern Ocean Biogeochemical Divide (SOBD) is the boundary between the two cells in the surface of the Southern Ocean, but its location is poorly constrained. Localizing the SOBD is important because biological nutrient utilization north and south of the SOBD have fundamentally different consequences for global ocean primary production and carbon sequestration. Here, we aim to localize the SOBD by releasing virtual Lagrangian particles south of 40°S in an eddying ocean sea-ice model and compare simulation results with observations. We find that the SOBD is a circumpolar band, where different sectors are shaped by different oceanographic features: (a) Ekman transport, (b) the γ = 27.6 kg m −3 neutral density outcrop, and (c) fronts associated with the Antarctic Circumpolar Current. Our findings help to understand how nutrient utilization in different parts of the Southern Ocean affects the biologically driven carbon sequestration.